Perubahan Histopatologi Kulit Ikan Koi (Cyprinus carpio) yang Terinfestasi Ichthyophthirius multifiliis Secara Kohabitasi [Skin Histopathology Alteration of Koi (Cyprinus carpio) With Ichthyophthirius multifiliis Infested Accordance Cohabitation] - Gunanti Mahasri; Lyla Wulandari; Kismiyati Kismiyati (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
AbstractKoi (Cyprinus carpio) is one of the most famous freshwater ornamental fish which offers financial advantage. There are a lot of factors which have to be face when we're trying to cultivate or culture Koi, one of those factors is the disease. Parasite which always in freshwater fishes is Ichthyophthirius multifiliis. I. multifiliis penetrated through skin causing destruction ephitelium cells by cilia and by consequent causing a histopathological changing. The objectives of this research was to determine alteration of Koi (Cyprinus carpio) skin histopathology which infested by I. multifiliis through cohabotation. Cohabitation was done during 4 days with mixing 7 fishes infected with white spot disease to 100 healthy fishes. Koi that had been infested observing of pathology changes. And than slicing the skin organ to prepare histopatology slide from 3 sample in every level infestation. To detect the level infestation, parasite was divide into 3 level respectivelly are low level (1-5 parasite/slide), the medium level (6-10 parasites/slide) and the heavy level (more than 11 parasites/slide). Furthermore, damage level determination by histopatology was decided by scoring. Data analyzed with descriptive based on clinical simptom, and than, the skin histopatology which had been attacked was done by scoring. The results would be analyzed statistical with Kruskal Wallis test. If it is show the significant defference, the test would be continued with Z test 5% (Siegel, 1986). The research showed that the fish skin Koi infestation by I. multifiliis there was histopatology changed shaped respectivelly epidermis proliferation, infiltration of inflammation cell and ephithel erosion. Based on histopatological changed skoring caused by I. multifiliis infestation from various infestation grade, there were 62.2% of Koi fish skin was epidermis proliferasi, 73.3% of one was infiltration of inflammation cell and 28.9% ephithel erosion. Water quality measurement showed that temperature and acidity in normal condition, respectively otemperature between 24–26 C dan pH 8.